2020
DOI: 10.1007/978-3-030-59025-3_13
|View full text |Cite
|
Sign up to set email alerts
|

An SMT-Based Concolic Testing Tool for Logic Programs

Abstract: Concolic testing combines symbolic and concrete execution to generate test cases that achieve a good program coverage. Its benefits have been demonstrated for more than 15 years in the case of imperative programs. In this work, we present a concolic-based test generation tool for logic programs which exploits SMT-solving for constraint resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We plan to investigate heuristics to distinguish both cases. Another interesting avenue for future research is to combine our approach with more directed testing techniques, such as, e.g., concolic testing [17].…”
Section: Discussionmentioning
confidence: 99%
“…We plan to investigate heuristics to distinguish both cases. Another interesting avenue for future research is to combine our approach with more directed testing techniques, such as, e.g., concolic testing [17].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Fortz et al (2020) essentially showed that one could rely on an SMT solver to implement a concolic testing tool for Prolog. The paper is focused on designing a more efficient alternative implementation of contest, as well as trying to avoid the unsoundness of the original approach by Mesnard et al (2015a).…”
Section: Related Workmentioning
confidence: 99%